2016
DOI: 10.2106/jbjs.15.00948
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Quantification of Stabilizing Effects of Subtalar Joint Soft-Tissue Constraints in a Novel Cadaveric Model

Abstract: If calcaneofibular ligament insufficiency is established, its reconstruction or repair should receive priority over that of other ankle or subtalar periarticular soft-tissue structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 27 publications
5
54
0
Order By: Relevance
“…The dual fluoroscopic imaging system demonstrated the altered kinematics of FAI patients during dynamic activities. These joint kinematic changes were similar to lateral ankle ligament compromised foot in previous in vitro studies . The LAS copers were also associated with ankle inversion during foot strike.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The dual fluoroscopic imaging system demonstrated the altered kinematics of FAI patients during dynamic activities. These joint kinematic changes were similar to lateral ankle ligament compromised foot in previous in vitro studies . The LAS copers were also associated with ankle inversion during foot strike.…”
Section: Discussionsupporting
confidence: 83%
“…The calcaneofibular ligament is associated with both tibiotalar and subtalar joint inversion/eversion stability . A carefully designed in vitro study reported increased subtalar inversion and external rotation after calcaneofibular ligament sectioning . Interosseous ligament sectioning substantially increases the subtalar anterior translation, inversion, and internal rotation .…”
Section: Discussionmentioning
confidence: 99%
“…2 Two ligaments are the primary stabilizers of the subtalar joint: the interosseous talo-calcaneal ligament (ITCL) and the calcaneo-fibular ligament (CFL). [6][7][8][9] Other ligaments providing subtalar joint stability include the cervical ligament, lateral talo-calcaneal ligament, and deltoid ligament. [6][7][8]10,11 Recent cadaver studies showed that the CFL is potentially the most important stabilizer of the subtalar joint when subjected to inversion and external rotation stress.…”
mentioning
confidence: 99%
“…[6][7][8][9] Other ligaments providing subtalar joint stability include the cervical ligament, lateral talo-calcaneal ligament, and deltoid ligament. [6][7][8]10,11 Recent cadaver studies showed that the CFL is potentially the most important stabilizer of the subtalar joint when subjected to inversion and external rotation stress. 7,8 As the CFL crosses both the ankle and subtalar joint, the stability of both joints is affected after injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation